Socioekonomické aspekty nezaměstnanosti - Volejníková Jolana (Univerzita Pardubice, 2007)
The aim of this article is to refer to problems of unemployment from different perspective than the unemployment is in most of cases presented. It is concerned about estimation of job applicants in term of their real availability/unavailability, detection of reasons of their evidence on employment office, respectively, detection of main reasons that classify job applicants as unavailable job applicants and analysis of their possibilities in term of assert on labour market.
Keywords: Labour Market; Unemployment; real availability of job applicants; real unavailability of job applicants; rate of unemployment